Endocrine predictors of testicular biopsy efficacy in patients with azoospermia - V. A. Toropov; S. Yu. Borovets; S. Kh. Al’-Shukri; A. M. Gzgzyan; V. Ya. Belousov; I. D. Fedorova (Вестник хирургии имени И.И. Грекова, 2017)
OBJECTIVE. The study identified predictors of endocrine detection of sperm in case of open testicular biopsy in patients with non-obstructive azoospermia. MATERIAL AND METHODS. The research was based on the results of examination and testicular biopsy of 76 patients with secretory azoospermia aged from 20 to 55 years old. The instrumental, laboratory, physical methods of research were carried out for all the patients before performing of the open biopsy for testicular sperm extraction. Hormone levels were determined in blood plasma such as luteinizing hormone, follicle stimulating hormone, prolactin, total and free testosterone, estradiol and sex steroid binding globulin. Patients were divided into two groups. The first group consisted of patients (n =43) whom sperms were found in testicular biopsies. The second group included patients (n = 33) whom sperms weren’t detected. RESULTS. Сonсentration of follicle stimulating hormone in blood plasma was the most significant hormone predictor. It was found that follicle stimulating hormone level between 12 and 16 IU/L indicated to the low probability of sperm presence in testicular biopsies and in case it was less than 17 IU/L the probability was extremely low. There was also established that elevated follicle stimulating hormone levels in patients older than 26 years pointed to the low probability of finding sperm using open testicular sperm extraction. CONCLUSIONS. Increase of luteinizing hormone, follicle stimulating hormone or their correlation in blood plasma indicates to a low probability of finding sperm by open testicular sperm extraction. The concentrations of testosterone, sex steroid binding globulin, prolactin and estradiol in the blood plasma weren’t reliable predictors of finding sperm in testicular biopsies.